KARAKTERISTIK HABITAT, POLA SEBARAN DAN PERILAKU MUSANG MENTAWAI (Paradoxurus lignicolor Miller 1903) DI AREA SIBERUT CONSERVATION PROGRAM, PULAU SIBERUT, KEPULAUAN MENTAWAI, SUMATERA BARAT - Abdul Haris Mustari; Dede Hendra Setiawan (Media Konservasi, 2013)
Mentawai palm civet (Paradoxurus lignicolor) is endemic to Mentawai Islands and one of its stronghold population is Siberut Island. This study was conducted in Siberut Conservation Programme Forest Area from May to August 2007.  The objectives of this study were to reveal habitat characteristics, population size, distribution pattern, and feeding behaviour of Mentawai palm civet.  A total of 125 plant species recorded in the study area, 21 species of which were identified as food plants for the Mentawai palm civet.  The dominant plant species in the Mentawai palm civet habitat were gutgut (Coccoseras borneensis), alosit (Baccaurea parviflora), and sibeumunte (Syzygium cf. palembanicum).  The civet was mainly observed at 4 - 20 m above of  the forest floor, which was the C stratum of the forest canopy.  Six individuals of Mentawai palm civet were directly encountered during the study and the estimated population density was 6.5 individuals/km 2.  The distribution pattern of the civet was clumped, yet the animals were solitary when foraging and other of their daily activities. The civets were frequently observed eating fruits of bu’bu’ lonjong (Palaquium sp.), bu’bu’ bulat (Baccaurea sp.), tumu (Buchanania arborescens), angglu (Rhapidopora sylvestris), langkap (Arenga obtusifolia), lambo (Ficus sp.), papaya (Carica papaya), and banana (Musa sp.).  Mentawai palm civets were observed foraging and  feeding  during day and night times, suggesting that the civet were both diurnal and nocturnal animal.  Keywords: Mentawai palm civet, habitat characteristics, distribution pattern, feeding behaviour